'Getting shut down and shut out': Exploring ACB patient perceptions on healthcare access at the physician-patient level in Canada. Issue 1 (31st December 2022) - Fante-Coleman, Tiyondah; Wilson, Ciann L.; Cameron, Ruth; Coleman, Todd; Travers, Robb
ABSTRACT: Purpose: The experiences of African, Caribbean and Black (ACB) Canadians are seldom explored in the Canadian context. Family physicians act as a gateway to the rest of the healthcare system and are necessary to provide proper patient care. However, Canada's history with colonialism may impact the socio-cultural context in which patients receive care. Method: 41 participants from Waterloo Region, Ontario, were engaged in eight focus groups to discuss their experiences in the healthcare system. Data were analysed following thematic analysis. Results: Style of care, racism and discrimination and a lack of cultural competence hindered access. oor Inadequate cultural competence was attributed to western and biomedical approaches, poor understanding of patients' context, physicians failing to address specific health concerns, and racism and discrimination. Participants highlighted that the two facilitators to care were having an ACB family physician and fostering positive relationships with physicians. Conclusion: Participants predominantly expressed dissatisfaction in physicians' approaches to care, which were compounded by experiences of racism and discrimination. Findings demonstrate how ACB patients are marginalized and excluded from the healthcare syste Iimplications for better access to care included utilizing community healthcare centres, increasing physicians' capacity around culturally inclusive care, and increasing access to ACB physicians.